1995
DOI: 10.1007/bf01876186
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutation of rhodopsin gene codon 15 found in Japanese autosomal dominant retinitis pigmentosa

Abstract: SummaryHeterozygous missense mutation in codon 15 of the rhodopsin gene was detected in a patient with autosomal dominant retinitis pigmentosa (ADRP), where a transition of adenine to guanine at the second nucleotide in codon 15 (AAT~AGT), corresponding to a substitution of serine residue for asparagine residue (Asn-15-Ser) was detected. None of the remaining unrelated 42 ADRP, 24 autosomal recessive RP (ARRP) and 34 normal individuals had this alteration. Her funduscopic findings were sectorial in type simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Consistent with previous reports, the most common single genes that were found to cause RP in this study are USH2A 2 , RPGR 33 , ABCA4 34 , and RP1 35 . The frequency of the mutations that were detected in RHO was lower than in Caucasians (8–25%) 2, 4, 36 , but was similar to reports in Japanese (∼1%) 37 and Indians (∼1%) 38 . Other genes caused only a small proportion of cases.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with previous reports, the most common single genes that were found to cause RP in this study are USH2A 2 , RPGR 33 , ABCA4 34 , and RP1 35 . The frequency of the mutations that were detected in RHO was lower than in Caucasians (8–25%) 2, 4, 36 , but was similar to reports in Japanese (∼1%) 37 and Indians (∼1%) 38 . Other genes caused only a small proportion of cases.…”
Section: Discussionsupporting
confidence: 84%
“…We attribute these differences between the WT and T4R opsins to the positive charge at Arg 4 resulting from the mutation and not the subsequent lack of glycosylation at Asn 2 , as bovine deglycosylated Rho in our assays showed very similar properties to WT Rho. However, lack of glycosylation at Asn 15 may cause other cell biological problems, as a substitution of Ser for Asn (N15S) was identified in a patient with autosomal dominant RP (70,71). In the case of human N15S and dog T4R mutations, the degeneration occurs within distinctive topographic regions (sectorial RP) (22, 70 -72) that could be related to differences in light exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Although it only targeted exons with known mutations, the study failed to identify high frequency RP genes [11] . Another study of the Japanese RP population focused on the RP genes RHO [12] [14] and EYS [15] , [16] , and found that EYS was a frequent arRP gene with a prevalence rate of 9% to 16% [15] , [16] . However, almost all reported EYS gene mutations in these studies have not been reported in Western populations suggesting that Japanese individuals have a different genetic background [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%